1996
DOI: 10.1002/(sici)1097-4547(19961201)46:5<581::aid-jnr7>3.0.co;2-f
|View full text |Cite
|
Sign up to set email alerts
|

Detection of increased tissue concentrations of nerve growth factor with an improved extraction procedure

Abstract: Nerve growth factor (NGF) is a protein essential for the survival and normal function of sympathetic neurons. Two‐site immunoassays have been developed over the past decade in several laboratories and used to estimate its endogenous concentrations in a variety of effector tissues. However, levels appear restricted to a narrow range, display only a poor correlation with innervation density, and show obvious inter‐ and intralaboratory variations, the origins of which are unclear. This led us to examine alternati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
27
1

Year Published

1997
1997
2009
2009

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(33 citation statements)
references
References 65 publications
5
27
1
Order By: Relevance
“…However, this study did not determine NGF levels in the primary sensory neurons after ischemia. In our current study, the ELISA method was used to assess NGF levels in DRG neurons as reported previously (53). The femoral artery occlusion elevated NGF in the DRG, and 24 and 48 h of postocclusion significantly increased NGF levels in the DRG of ischemic rats.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…However, this study did not determine NGF levels in the primary sensory neurons after ischemia. In our current study, the ELISA method was used to assess NGF levels in DRG neurons as reported previously (53). The femoral artery occlusion elevated NGF in the DRG, and 24 and 48 h of postocclusion significantly increased NGF levels in the DRG of ischemic rats.…”
Section: Discussionsupporting
confidence: 88%
“…We chose to harvest the L4-L6 DRGs because they largely innervate the hindlimb muscles studied in this experiment. NGF levels were determined using a two-site immunoenzymatic assay (ELISA) as previously described (53). It is noted that the ELISA measurements were made on L4-L6 DRGs from individual animals.…”
Section: Femoral Artery Ligationmentioning
confidence: 99%
“…The homogenized tissue was centrifuged for 20 min at 14,000 rpm. The NGF Emax Immunoassay system ELISA-kit (Promega, Mannheim, Germany) was employed on the extracted supernatent according to the protocol provided by the manufacturer (Zettler et al 1996). We performed measurements in pilot experiments on normal skin by taking different pieces of adjacent back skin.…”
Section: Evaluation Of Ngf Contentmentioning
confidence: 42%
“…These results are consistent with a number of independent published findings of high NGF in the SHR strain. 3,4,[7][8][9][10]15 However, the new finding in the present study is that this increased level of NGF mRNA is associated with the inher- …”
Section: Discussionmentioning
confidence: 99%